THE SYSTEM OF MONITORING LEVELS OF GASES SUCH AS CARBON MONOXIDE (CO) IS IN THE AIR - Tahir, Tamus bin (Department of Electrical Engineering, University of Patria Artha, 2017)
This research aims to monitor carbon monoxide gas, thus obtained data about the presence of carbon monoxide gas in the air as well as the location of the place of monitoring and displayed in a web form with the addition of maps in real time. This system consists of DT-Sense Carbon Monoxide Sensor used to detect carbon monoxide gas, GPS/GSM/GPRS and a microcontroller as the pemproses sensor data and data from GPS position which is then sent to the web server via the Internet. This website is displayed in the form of a point on a digital map that contains carbon monoxide gas information, date and time of the measurement.Â Â